An analysis of non-performing loan, interest rate and inflation rate using Stata software - Abu Hassan Asari, Fadli Fizari; Muhamad, Nurul Afifah; Ahmad, Wardiyyah; Abd Latif, Nurul 'Izzati; Abdullah, Norashikin; Jusoff, Kamaruzaman (IDOSI Publications, 2011)
Non-performing loan can be defined as defaulted loan in which banks are unable to profit from. Usually loan falls due if no interest has been paid in 90 days, however this may vary between different countries and actors. The purpose of this paper is to analyze the relationship between the non-performing loan, interest rate and inflation rate by utilizing STATA software. In order to achieve this objective, the Vector Error Correction Model (VEC1.1) is employed to determine whether interest rate and inflation rate may affect the nonperforming loan based on a 48 monthly data. The long run relationship shows that interest rate has a significant relationship towards non-performing loan. On the other hand, there is an insignificant relationship between inflation rate and non-performing loans. In the short run relationship, the findings show that both independent variables cannot influence the non-performing loan. Both independent p-values are less than significant interval which means this result will not reject the null hypothesis. As a conclusion, the causal relationship between non-performing loans and inflation rate is nodirectional relationship where similar with the causality relationship between non-performing loans and base lending rate. This research is appertained with commercial banks in Malaysia, thus a restored interpretation in this study will lead to a progressing association in the future.